Science of ICT: computer as a Qalam - Abdul Latif, Nur Zahidah (2014)
The paper aims to discuss on how computer replacing the Qalam or in other word, pen as a medium of knowledge transferring. Pointed out from Surah (Al-Alaq, 96:1-5), "Proclaim! (Or read) in the name of thy Lord and Cherisher, who created, created man out 0f (mere) clot of congealed blood. Proclaim! And thy Lord is Most Bountiful — He who taught (the use of) the pen, Taught man that which he knew not.”, clearly mentioning the word Qalam (pen) as a tool in seeking knowledge. In today’s Muslim world, the word Qalam infers to the computer. The paper will look into both function of Qalam and computer and the relationship between both. Indeed, computer functioning as a Qalam is able to assist human beings in becoming an insan guided by the Quran and Sunnah. Nevertheless, another important aspect to be discussed in the paper is on the transition of knowledge captured from the ICT point of view. There are four (4) stages of the transition of knowledge that related to the science of ICT which is data, information, knowledge and wisdom. Each of the transition stages is related with the book of Allah which is Al-Quran. The subsection in the paper will further explain the connection between those transition and Ayah in the Holy Quran.